A method for calibration of the Hyperplastic Accelerated Ratcheting Model (HARM). (August 2019) - Abadie, C.N.; Houlsby, G.T.; Byrne, B.W.
Abstract: This paper presents an analytical methodology for calibration of the Hyperplastic Accelerated Ratcheting Model (HARM, Houlsby et al., 2017 [3]), based on a closed-form expression for the accumulation of ratcheting strain with cyclic history. The proposed method requires the fit of one test response and of a few continuous cyclic tests. The initial motivation for this work is the calibration of models for the design of piles subjected to long-term cyclic lateral loading, and the test results from Abadie et al. (2018, 2015) [1, 2] are used for calibration and proofing of the model. Nevertheless, the method is applicable to other problems of similar behaviour.